Management of Idiopathic Thrombocytopenic Purpura in Adult: A Review Article - Rahaman, Mohammad Ferdous Ur; Rahman, Farzana; Salman, Mohammad; Kader, Md. Abdul; Azad, Md. Abdul Kalam (Journal of Shaheed Suhrawardy Medical College, 2012)
Idiopathic thrombocytopenic purpiira (ITP), also known as primary immune or autoimmune thmmbocytopenic purpura, is a common cause of thrombocytopenia and bleeding complications in children and adults. It mav be confused with other causes of thrombocvtopenia and is treated with agents that varv in efjicacv, toxicity, and cost. Clinical presentation very in children and adult. In children, ITP is usually an acute, self-limited disorder that resolves spontaneously: in adults, it is typically a chronic disorder with a more insidious onset. In about one third of adults with ITP, the condition is persistent and relatively resistant to most treatments .Available evidence suggests that only about 5% of adults with chronic ITP have spontaneous remission. The principal therapeutic options for ITP include glucocorticoids, intravenous immunoglobulin and splenectomy. Other treatments have been used for refractory cases; these include intravenous anti-Rh (D), azathioprine, cyclophosphamide, danazol, vinca alkaloids, ascorbic acid, colchicine, interferon-alpha, combination chemotherapy, protein A, immunoadsorption, cyclosporine, epsilon-aminocaproic acid, plasma exchange, and accessory splenectomy. Journal of Shaheed Suhrawardy Medical College Vol 2No.1 June 2010 page 24-28 DOI: http://dx.doi.org/10.3329/jssmc.v2i1.12348